\(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\)=\(\frac{a+b+c}{b+c+a}\)
=> a=b=c
=>\(\frac{-2}{19}b+\frac{5}{53}c=\frac{-2}{19}\times2014+\frac{5}{53}\times2014=-212+190=-22\)
\(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\)=\(\frac{a+b+c}{b+c+a}\)
=> a=b=c
=>\(\frac{-2}{19}b+\frac{5}{53}c=\frac{-2}{19}\times2014+\frac{5}{53}\times2014=-212+190=-22\)
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\); a+b+c\(\ne\)0 và a=2014
Khi đó \(a-\frac{2}{19}b+\frac{5}{53}c\)=....
Cho:\(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\)a+b+c khac 0va a=2014.Khi do\(a-\frac{2}{19}b+\frac{5}{53}c\)la
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\); a + b + c khác 0 ; a = 2014. khi đó \(a-\frac{2}{19}b+\frac{5}{33}c=...\)
\(giải hộ mình nhớ ghi cách làm\)
\(cho\frac{a}{b}=\frac{b}{c}=\frac{c}{a'};a+b+c\ne0vàa=2014.khiđóa-\frac{2}{19}b+\frac{5}{53}c\)
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\); a+b+c khác 0 và a=2014
Khi đó: a-\(\frac{2}{19}b+\frac{5}{33}c\)=.....
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a};a+b+c\ne0vàa=2014\)
khi đó \(a-\frac{2}{19}b+\frac{5}{13}c=....\).
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\); a+b+c khác 0 và a=2014
Khi đó a-\(\frac{2}{19}\)b+\(\frac{5}{33}c\)=......
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\) ;a+b+c\(\ne\)0 và a=2014
Khi đó a-\(\frac{2}{19}b+\frac{5}{33}c=\).....
giúp mk nha mấy bạn mk xin cảm ơn trước hậu tạ sau nghen
Cho \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a};a+b+c\ne0\). khi đó a.b.c=...